Sensing the Difference: The Influence of Anisotropic Cues on Cell Behavior - Ballester-Beltrán, José; Biggs, Manus J. P.; Dalby, Matthew J.; Salmerón-Sánchez, Manuel; Leal-Egaña, Aldo (Frontiers in Materials, 2015)
From tissue morphogenesis to homeostasis, cells continuously experience and respond to physical, chemical and biological cues commonly presented in gradients. In this article we focus our discussion on the importance of nano/micro topographic cues on cell activity, and the role of anisotropic milieus play on cell behavior, mostly adhesion and migration. We present the need to study physiological gradients in vitro. To do this, we review different cell migration mechanisms and how adherent cells react to the presence of complex tissue-like environments and cell-surface stimulation in 2D and 3D (e.g. ventral/dorsal anisotropy).